ANALISIS KINERJA BIDANG PENGENDALIAN OPERASIONAL (DALOPS) DI DINAS PERHUBUNGAN KOTA DUMAI - Nurhasanah D.R; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Dumai City Transportation Department is one of the agencies having duties and responsibilities in the effort to promote and build the transportation sector, with the many development progress reaching the outskirts or to the outskirts of Dumai City, marked by the high mobility of people / goods doing travel activity / movement from one place to another place every day on a regular basis. The Department of Transportation has the duty to exercise authority in the field of transportation in the sense of formulating policies, coordinating, fostering, organizing and controlling the administration of government tasks, development, public services, licensing, user charges, service standardization, data and information management, accident prevention and handling, Education and socialization of regulation and safety program of transportation field, implementation of traffic management and management, arrangement and control of traffic, patrol and escort of field of road and road transport, inspection of technical requirement and the goodness of transportation facilities and infrastructure, discipline development, Implementation of investigation and law enforcement in the field of transportation.This research uses qualitative research method by studying data descriptively. The concept of theory using the concept of performance theory Agus Dwiyanto (2006: 50) and Hasibuan (2003: 244). In data collection, researchers used interview techniques, observation and documentation. By using Purposive as a source of information and data analysis techniques using descriptive qualitative techniques.The results of this study indicate that the performance of Operational Control Sector (Dalops) is still not working optimally. There are still employees who work not in accordance with its function and follow the vision of the mission of the Department of Transportation Dumai City. Operational Control Officers (Dalops) also have the ability / level of education that is not in accordance with the job description. Required training for office employees to improve the performance and ability of employees of Operational Control Sector (Dalops) to comply with the Vision and Mission of Dumai City Transportation Department.Keywords:Performance, Vision and Mission, Productivity, Effectiveness